2021
DOI: 10.3390/biomedicines9050543
|View full text |Cite
|
Sign up to set email alerts
|

PPARgamma: A Potential Intrinsic and Extrinsic Molecular Target for Breast Cancer Therapy

Abstract: Over the last decades, the breast tumor microenvironment (TME) has been increasingly recognized as a key player in tumor development and progression and as a promising prognostic and therapeutic target for breast cancer patients. The breast TME, representing a complex network of cellular signaling—deriving from different stromal cell types as well as extracellular matrix components, extracellular vesicles, and soluble growth factors—establishes a crosstalk with cancer cells sustaining tumor progression. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PPAR-γ is frequently expressed in various cancer cells, including breast, lung, colon, lips, kidney, pancreatic and thyroid [ 32 ]. Several studies have revealed that PPAR-γ activation by its agonists imposes cell cycle arrest [ 33 ], apoptosis [ 34 ], angiogenesis [ 35 ], inhibition [ 36 ], and redifferentiation [ 37 ], which are the key molecular processes associated with the prevention of tumor growth and progression. The expression of angiogenesis-related proteins such as vascular endothelial growth factor (VEGF) and cyclooxygenase-2 as well as inflammatory mediators in the tumor microenvironment are all inhibited by PPAR-γ activation [ 38 ].…”
Section: Functional Diversity Of Ppar-γmentioning
confidence: 99%
“…PPAR-γ is frequently expressed in various cancer cells, including breast, lung, colon, lips, kidney, pancreatic and thyroid [ 32 ]. Several studies have revealed that PPAR-γ activation by its agonists imposes cell cycle arrest [ 33 ], apoptosis [ 34 ], angiogenesis [ 35 ], inhibition [ 36 ], and redifferentiation [ 37 ], which are the key molecular processes associated with the prevention of tumor growth and progression. The expression of angiogenesis-related proteins such as vascular endothelial growth factor (VEGF) and cyclooxygenase-2 as well as inflammatory mediators in the tumor microenvironment are all inhibited by PPAR-γ activation [ 38 ].…”
Section: Functional Diversity Of Ppar-γmentioning
confidence: 99%
“…Upon ligand binding, PPARs can modulate target gene expression by binding to the peroxisome proliferator responsive element (PPRE) in target genes [ 54 ]. Specifically, PPARγ activation inhibits tumor cell growth in vitro and in vivo model systems, suggesting the potential role of this receptor for cancer therapy [ 55 , 56 , 57 , 58 ]. Retinoids alone or in combination with PPARγ agonists are cell differentiation agents, which play a fundamental role in controlling cell proliferation and metabolism [ 59 , 60 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…PPARγ activation occurs through natural or synthetic ligands like ω-3 polyunsaturated fatty acids (PUFA) and thiazolidinediones (TZD). Upon activation, PPARγ forms a heterodimer with RXR, translocates to the nucleus, and binds to the PPRE of PPARγ target genes, initiating gene transcription and participating in the regulation of multiple gene expressions [ 142 ]. Studies specifically in breast cancer have revealed the significant role of ligand-bound PPARγ in inhibiting the growth, metastasis, and invasion of breast cancer cells, impacting cell cycle regulation, and influencing both endogenous and exogenous apoptosis across various breast cancer subtypes, including ER + /PR + , ER-/PR-, HER + , and triple-negative breast cancer cells [ 143 ].…”
Section: Introductionmentioning
confidence: 99%